2018
DOI: 10.1002/jlb.ma1217-499rr
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-mediated modulation of the hepatic miRNome: miR-146b-5p is an IL-6-inducible miRNA with multiple targets

Abstract: Interleukin-6 (IL-6)-type cytokines play important roles in liver (patho-)biology. For instance, they regulate the acute phase response to inflammatory signals and are involved in hepatocarcinogenesis. Much is known about the regulation of protein-coding genes by cytokines whereas their effects on the miRNome is less well understood. We performed a microarray screen to identify microRNAs (miRNAs) in human hepatocytes which are modulated by IL-6-type cytokines. Using samples of 2 donors, 27 and 68 miRNAs (out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
0
15
1
Order By: Relevance
“…Kirschmeyer et al observed, like us, that the expression profile of the gene in question can be regulated by miRNAs. They found that miR-146b-5p reduced the number of mRNA SLC10A3 copies [35], which was not confirmed by our research. Under the influence of the addition of adalimumab to culture, we have observed that hsa-miR-199a-5p potentially affects the expression of SLC10A3.…”
Section: Discussioncontrasting
confidence: 99%
“…Kirschmeyer et al observed, like us, that the expression profile of the gene in question can be regulated by miRNAs. They found that miR-146b-5p reduced the number of mRNA SLC10A3 copies [35], which was not confirmed by our research. Under the influence of the addition of adalimumab to culture, we have observed that hsa-miR-199a-5p potentially affects the expression of SLC10A3.…”
Section: Discussioncontrasting
confidence: 99%
“…We designed a library consisting of 538 miRNAs, which were selected from miRBase version (v.)21 by the following criteria: (1) presence in the high-confidence list from miRBase, 97 (2) predicted by Diana web server v.5.098, 99 to target molecule(s) related to IL-6 signaling, (3) presence in the top 100 list of miRNAs regulated upon hy-IL-6 stimulation in primary hepatocytes (microarray analysis, ArrayExpress: E-MTAB-6572), 100 and (4) miRNAs previously published as regulated by STAT3 (for a complete list, see Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, among the miRNAs predicted to recognize these polymorphic sites, none bind TG, but miR-3181 preferentially recognizes CG and miR-2861, CA. Both are expressed in the liver [49], with miR-2861 being up-regulated by interleukin 6 [50], a proinflammatory cytokine with a pivotal role in leprosy disease [51]. It is thus conceivable that these regulatory mechanisms operate after disease establishment and activation of the acute phase response (Fig 6).…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%